2017
DOI: 10.1074/jbc.m117.793539
|View full text |Cite
|
Sign up to set email alerts
|

A ciliary opsin in the brain of a marine annelid zooplankton is ultraviolet-sensitive, and the sensitivity is tuned by a single amino acid residue

Abstract: Ciliary opsins were classically thought to function only in vertebrates for vision, but they have also been identified recently in invertebrates for non-visual photoreception. Larvae of the annelid are used as a zooplankton model, and this zooplankton species possesses a "vertebrate-type" ciliary opsin (named c-opsin) in the brain. c-opsin is suggested to relay light signals for melatonin production and circadian behaviors. Thus, the spectral and biochemical characteristics of this c-opsin would be directly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 74 publications
(99 reference statements)
7
56
0
Order By: Relevance
“…Next, we expressed Platynereis c-opsin1 in COS1 cells, reconstituted it with 11-cis-retinal and purified it (Yokoyama, 2000). The reconstituted pigment absorbed in the UV range with a λ-max of 384 nm in the dark spectrum and a λ-max of 370 nm in the dark-light difference spectrum ( Figure 2E), in agreement with a recent report (Tsukamoto et al, 2017). To investigate how cPRCs respond to light, we did calcium imaging in larvae ubiquitously expressing the calcium sensor GCaMP6s (Chen et al, 2013;.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Next, we expressed Platynereis c-opsin1 in COS1 cells, reconstituted it with 11-cis-retinal and purified it (Yokoyama, 2000). The reconstituted pigment absorbed in the UV range with a λ-max of 384 nm in the dark spectrum and a λ-max of 370 nm in the dark-light difference spectrum ( Figure 2E), in agreement with a recent report (Tsukamoto et al, 2017). To investigate how cPRCs respond to light, we did calcium imaging in larvae ubiquitously expressing the calcium sensor GCaMP6s (Chen et al, 2013;.…”
Section: Resultssupporting
confidence: 90%
“…The pigmented eyes mediate early-and late-stage larval phototaxis (Gühmann et al, 2015;Jékely et al, 2008;Randel et al, 2014). The cPRCs in Platynereis have been proposed to regulate melatonin production and to entrain the circadian clock to ambient UV light (Arendt et al, 2004;Tosches et al, 2014;Tsukamoto et al, 2017). However, the function of the cPRCs in Platynereis and how they interact with rPRCs is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Of the two putative opsins found in Hirudo, one (Contig139791, Supplemental File) had BLAST hits with other invertebrate opsins outside of leeches that are sensitive to blue and green wavelengths; the other (Contig156444, Supplemental File) showed similarities to UV opsins from arthropods. We also performed a direct BLAST comparison against a previously described UV-sensitive from another annelid, Platynereis dumerilii (Tsukamoto et al, 2017), and found a close match between it and our putative UV opsin (Table S1).…”
Section: Transcriptomic Confirmation Of a Second Photoreceptormentioning
confidence: 78%
“…4a). Pdu -c-opsin1, is maximally photo-activated between 380 and 400 nm [25], and thus can be discounted from shadow detection due to a negligible wildtype shadow response at 400 nm light (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
“…The in vitro opsin absorption assay was conducted as described by Tsukamoto et al [25]. Briefly, native Platynereis c-opsin2 with the 1D4 tag (ETSQVAPA) on the C-termini was subcloned into the pMT vector.…”
Section: Methodsmentioning
confidence: 99%